Breach and restoration of retinal immune privilege: barrier failure, innate dysregulation, and adaptive autoimmunity - Fan, Qiwei; Li, Zhijie (Frontiers in Immunology, 2025)
The retina preserves vision by tightly regulating inflammation (“immune privilege”) via blood–retinal barriers, neuroglial checkpoints, and tolerogenic cues. This actively maintained—and potentially restorable—state is breached in major retinal diseases through three recurrent archetypes. We synthesize 2015–2025 advances into a framework of barrier failure, innate dysregulation, and adaptive autoimmunity. Across age-related macular degeneration (AMD), diabetic retinopathy (DR), retinitis pigmentosa (RP), and non-infectious uveitis (NIU): AMD exhibits complement–microglia para-inflammation with later outer-barrier compromise; DR exemplifies inner-BRB failure with inflammatory amplification; RP begins with degeneration-triggered innate activation and progresses to combined innate–adaptive injury; NIU represents T-cell-driven breach of the blood–retinal barrier. Interventional human evidence supports immunity as a therapeutic target: complement inhibition slows geographic atrophy; anti-VEGF reduces leak; intravitreal corticosteroids suppress inflammatory edema; and anti-TNF/IL-6R improve refractory NIU. Emerging strategies aim at privilege restoration—reinforcing myeloid checkpoints, tempering inflammasomes, and exploring tolerance-oriented approaches to re-educate adaptive immunity. Evidence from preclinical and early translational studies indicates that ocular tissues can imprint regulatory/anergic programs on pathogenic T cells, supporting mechanism-aligned, patient-tailored immunotherapy as a testable route to restore regulation, mitigate inflammation, and slow degeneration.